Effects of Electric Field Exposure on Microbiological and Physiochemical Quality in Climbing Perch (Anabas testudines) - Karim, Nurul Ulfah; Jusoh, Che Fatimah Nadia Che; Othman, Rohisyamuddin; Bolong, Abol Munafi Ambok; Hassan, Marina (Research Aspects in Agriculture and Veterinary Science Vol. 3, 2021)
Electric field exposure during fish harvesting at aquaculture farm or sampling site is one of the recommended stunning method that consistence with animal welfare. The objectives of these study are to determine the microbiological and psychochemical quality of climbing perch subjected to 50, 70, 90 and 110 V electroshock for 2 min and controls were left untreated. The bacteria count in climbing perch showed a significantly (p<0.05) reduced after stunned at 70-90 V. Meanwhile, stunning at 50 and 110 V were not comparatively different (p>0.05) to the untreated samples. Stunning at 50-110 V were not significantly (p<0.05) effects the pH value in climbing perch. Climbing perch stunned at 90-110 V showed a significantly (p<0.05) lower amount of total colour compared to the untreated samples and give a pale looks and discoloration to the fish flesh. It is suggested electric field exposure for fish harvesting at range 70-90 V, which significantly contributes to reduce microbial effects and giving a minimal appearance changes.